1479. Evaluating the Impact of Procalcitonin on Antibiotic Utilization in Chronic Obstructive Pulmonary Disease Exacerbations. (26th November 2018) - Lin, Kevin; Dempsey, Casey; Patel, Shivani; Butler, John; Septimus, Edward
Abstract: Background: Antibiotic prescription rates for treating exacerbations of chronic obstructive pulmonary disease (COPD) have been reported as high as 90% in the United States. Research has shown that over 50% of COPD exacerbations are due to viral etiologies. Elevations in procalcitonin (PCT) levels can be seen in bacterial infections and can help guide the need for antimicrobial therapy. The goal of this study is to evaluate the impact of PCT on antibiotic use in patients with COPD exacerbations. Methods: We conducted a retrospective, pre- and post-intervention study. Patients at least 18 years of age, with a diagnosis of COPD exacerbation, and had a PCT level drawn within 24 hours of admission were included. Exclusion criteria included patients presenting with severe trauma, sepsis, bacterial pneumonia, patients who required invasive mechanical ventilation, and patients with an initial admission to the ICU. The primary outcome was antimicrobial duration of therapy. Secondary outcomes included hospital length of stay (LOS), respiratory-related 30-day readmission rates, and treatment failure defined as ICU admission, requirement of invasive mechanical ventilation, or death. Results: A total of 139 patients were evaluated with 64 and 75 patients in the pre- and post-intervention cohorts, respectively. PCT guidance was associated with a significant reduction in number of antibiotic days of therapy (7.1 days vs. 2.4 days; P < 0.001). A trend in decreasing LOS was observed but did not reach statistical significance (5.3 days vs. 4.1 days; P = 0.080) and respiratory-related 30-day readmission rates did not differ (9.4% vs. 10.7%; P = 0.801). In addition, treatment failure defined as ICU admission (3.1% vs. 0%; P = 0.210), requirement for invasive mechanical ventilation (3.1% vs. 0%; P = 0.210), and death (1.6% vs. 0%; P = 0.460) did not differ significantly between groups. Conclusion: Implementation of a PCT-guided protocol for the treatment of COPD exacerbations was associated with a significant reduction in antimicrobial days of therapy. We noted a trend in decreasing LOS and no difference respiratory-related 30-day readmissions, or treatment failure. Our PCT-guided protocol has been demonstrated to safely reduce antibiotic utilization in patients with COPD exacerbations. Disclosures: All authors: No reported disclosures.